First Estimations of Cosmological Parameters From BOOMERANG - Lange, A E; Ade, P A R; Bock, J J; Bond, J R; Borrill, J; Boscaleri, A; Coble, K; Crill, B P; De Bernardis, P; Farese, P; Ferreira, P; Ganga, K; et al. (2001)
The anisotropy of the cosmic microwave background radiation contains information about the contents and history of the universe. We report new limits on cosmological parameters derived from the angular power spectrum measured in the Antarctic flight of the BOOMERANG experiment within the framework of inflation-motivated adiabatic cold dark matter models. Using a weak prior on the Hubble expansion parameter $h$ we find that the curvature is close to flat and the primoridal fluctuation spectrum is nearly scale invariant, in agreement with the basic inflation paradigm. We find that the data prefer a baryon density $Ω_b h^2$ above, though similar to, the estimates from light element abundances and big bang nucleosynthesis. When combined with large scale structure observations, the BOOMERANG data provide evidence for both dark matter and dark energy contributions to the total energy density $Ω_{tot}$.